Postglacial Emergence in Atlantic Canada - Wightman, David; Cooke, H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1978)
Summary Elevated marine features occur in Atlantic Canada and those that appear to represent the upper marine limit and have been dated cluster around 13,000 + 500 years B.P., with a range from 14,000 to 11,500 years B.P, Although the scatter of dates precludes the drawing of truly synchronous isobases, simple isopleths can be drawn and show regional variations in uplift that are probably related to ice loads Two main centres of maximum uplift are shown, namely New Brunswick, and northern Newfoundland - southeastern Labrador. The uplift in southwestern and northern New Brunswick is probably related to strong ice outflow in those areas, while thick Labrador ice caused rebound to increase towards the north in Newfoundland, A northward deflection of the isopleths in the Gulf of St. Lawrence suggests that it was free of grounded ice during the late Wisconsman.